Research on the process of crack growth induced by explosion stress waves in rock masses with open joints. (October 2021) - Wang, Yanbing; Ren, Bin; Wang, Dongchen
Highlights: PMMA medium with vertical open joints under explosion loading was conducted. Study the stress wave propagation. Different dip angle of joints were examined using DLSM. Abstract: A joint in the medium has a significant impact on the propagation of explosion stress wave and the growth of explosion-induced crack. In this work, the crack growth experiment in the PMMA(polymethyl methacrylate) medium with vertical open joints under explosion loading was first carried out on the digital laser dynamic caustics experimental system (DLDC), in order to analyze the crack initiation, growth and arrest of wing cracks, and examine how the DSIF(dynamic stress intensity factor) at crack tip and the velocity of crack growth changed. The process of stress wave propagation and crack growth in this experiment was effectively inverted using the discrete lattice spring model (DLSM), the stress changes at the midpoint and endpoint of the joint were compared, and the acting characteristics of stress wave were analyzed here. Finally, the differences in velocity and acceleration of crack growth of wing cracks were compared and examined under different dip angles of joints.